(untitled) (Jurnal Bawaslu Provinsi Kepulauan Riau, 2025)
This study aims to analyze the effectiveness of the Election Supervisory Board (Bawaslu) of Riau Islands Province in ensuring voter data accuracy during the 2024 Regional Head Election. Using a qualitative descriptive method with an institutional case study approach, data were collected from seven regencies/cities throughout the Riau Island Province. Through monitoring reports, corrective recommendations, and plenary results on the Provisional Voters List (DPS), the Improved DPS (DPSHP), and the Final Voters List (DPT). Findings show that Bawaslu effectively implemented evidence-based supervision, strengthened coordination with the Election Commission (KPU) and Civil Registry (Disdukcapil), and ensured administrative follow-up to recommendations. Challenges included high population mobility, data synchronization issues, and unremoved deceased voters. Nonetheless, tiered supervision and data-driven reporting significantly improved the accuracy of the Final Voters List (DPT).